2021
DOI: 10.3390/children8080718
|View full text |Cite
|
Sign up to set email alerts
|

sFlt-1/PlGF Ratio in Prediction of Short-Term Neonatal Outcome of Small for Gestational Age Neonates

Abstract: Background: Small for gestational age is a pregnancy complication associated with a variety of adverse perinatal outcomes. The aim of the study was to investigate if sFlt-1/PlGF ratio is related to adverse short-term neonatal outcome in neonates small for gestational age in normotensive pregnancy. Methods: A prospective observational study was conducted. Serum sFlt-1/PlGF ratio was measured in women in singleton gestation diagnosed with fetus small for gestational age. Short-term neonatal outcome analyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
2
9
1
1
Order By: Relevance
“…23 In particular, the study from Garcia-Manau et al 27 reports a positive ratio in 21.5% of patients with early FGR in stage I. Quezada et al, 26 however, in a cohort of early FGR pregnancies, reported an even higher rate (75% positive sFlt1/PlGF ratios), with a mean ratio value of 196 (whereas in our cohort, mean sFlt1/PlGF was 91.2). We hypothesize that our population is more similar to the stage I population described in the former study by Garcia-Manau et al 27 Looking at the correlation between sFlt1/PlGF ratio and latency to delivery/fetal demise, it was clear that a higher ratio predicts a faster fetal deterioration and an earlier delivery/fetal demise for early FGR fetuses, even after excluding deliveries for maternal indications and controlling for confounders (occurrence and S3). When considering the cut-off described in the literature for ratio positivity, a positive ratio significantly correlates with an earlier delivery/fetal demise and shorter latency to delivery/fetal demise (Table S2).…”
Section: Maternal Characteristicsmentioning
confidence: 44%
See 2 more Smart Citations
“…23 In particular, the study from Garcia-Manau et al 27 reports a positive ratio in 21.5% of patients with early FGR in stage I. Quezada et al, 26 however, in a cohort of early FGR pregnancies, reported an even higher rate (75% positive sFlt1/PlGF ratios), with a mean ratio value of 196 (whereas in our cohort, mean sFlt1/PlGF was 91.2). We hypothesize that our population is more similar to the stage I population described in the former study by Garcia-Manau et al 27 Looking at the correlation between sFlt1/PlGF ratio and latency to delivery/fetal demise, it was clear that a higher ratio predicts a faster fetal deterioration and an earlier delivery/fetal demise for early FGR fetuses, even after excluding deliveries for maternal indications and controlling for confounders (occurrence and S3). When considering the cut-off described in the literature for ratio positivity, a positive ratio significantly correlates with an earlier delivery/fetal demise and shorter latency to delivery/fetal demise (Table S2).…”
Section: Maternal Characteristicsmentioning
confidence: 44%
“…Mean gestational age at diagnosis of FGR in our cohort (27.2 gestational weeks) was similar to previous reports. 26,27 In agreement with TA B L E 1 Description of the study population (early FGR pregnancies) regarding maternal, pregnancy, delivery and newborn characteristics.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Chang et al have already shown that infants with a high maternal sFlt-1/PlGF ratio above 85 had a lower birth weight (1142 ± 472 g vs. 2311 ± 236 g, p<0.001) and a higher risk for prematurity, BPD and respiratory distress syndrome (RDS) compared to the low ratio group (13). Also, Witwicki et al demonstrated that children of women with a sFlt-1/PlGF ratio ≥33 were significantly smaller, had more respiratory and gastrointestinal morbidity, and longer hospitalization (44). A relationship between a high ratio and low birth weight was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Witwicki et al. demonstrated that children of women with a sFlt-1/PlGF ratio ≥33 were significantly smaller, had more respiratory and gastrointestinal morbidity, and longer hospitalization ( 44 ). A relationship between a high ratio and low birth weight was also shown in our study.…”
Section: Discussionmentioning
confidence: 99%